COVID-19 and SARS-CoV-2: Everything we know so far – A comprehensive review - Naz Sumaira (De Gruyter, 2021)
Coronavirus disease-2019 (COVID-19) emerged as a unique type of pneumonia outbreak in the Wuhan city of China in 2019 and spread to all its provinces in a matter of days and then to every continent of the world except Antarctica within 3–4 month. This paper aims to comprehensively consolidate the available information about COVID-19 and present all the possible information about this disease in form of a single paper to readers. Unparalleled research and exhaustive studies of everything about the disease and its causative virus, i.e., severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), are underway since its emergence. The genome sequence of the virus was made available within a record short time by China, making possible immediate study of its structure and characteristics. The routes of transmission of the disease, signs and symptoms, incubation period, pathogenesis, and pathophysiology have been extensively studied and presented in an organized way in this review paper. The number of confirmed cases and case fatality and mortality rates are updated regularly. The different diagnostic mechanisms have been characterized. Testing and management criteria and protocols have been adopted. Extensive efforts are underway for finding a treatment of the disease and developing a vaccine against it. A number of vaccines are available even in markets in different countries. More and more ways of personal protection, prevention, and mitigation of the disease are being explored and shared. While the outbreak has been declared as pandemic, the response of scientists was timely and enormous; thousands of publications about various aspects and impact of the diseases and its causative virus are there on the World Health Organization database and many more studies are underway. The purpose of writing this review article is to provide a comprehensive summary of the major aspects and important scientific findings so far, about COVID-19 and SARS-CoV-2, in a single article for ready reference.